Personal, Interpersonal, and Sociocultural Factors of Condom Use in Rural Indigenous Nahuas Adolescents in Mexico - Raquel A. Benavides-Torres; María de los Ángeles Meneses-Tirado; Alan Josué Ramírez-Calderón; Dora Julia Onofre-Rodríguez; Jane Dimmitt Champion (Children, 2023)
The goal of this research was to determine the personal, interpersonal, and sociocultural predictors of condom use among rural Indigenous adolescents. Predictor variables were selected from Bandura’s Social Cognitive Theory and Leininger’s Transcultural Theory. The sample consisted of 419 Nahuas adolescents randomly selected from the total number of neighborhood blocks in a rural community in Puebla, Mexico. The instruments had acceptable psychometric characteristics (Cronbach alpha and validity scores). Multiple linear regression models were used. Results: 56.8% of participants were female, and 50.40% were students. Mean age was M = 17.5 (SD = 0.97), and the majority (63%) identified as Catholic. Age at menarche/first ejaculation (β = −1.2, p = 0.038), attitude toward condom use (β = 0.13, p < 0.001), ethnic identity (β = 0.21, p < 0.001), and ability to negotiate condom use (β = 0.13, p = 0.003) predicted (R2 = 22.3) condom use. This study provided a basis for integration of the cultural values of Indigenous adolescents within interventions for sexual health promotion.